The Concept of Touching Animals or Market? - Irina Ivleva (Journal of Economic Sociology, 2023)
For some time, pets remained relatively invisible in social sciences, despite their significant social functions. However, in recent decades, there has been a phenomenon known as the “animal turn,” marked by the development of anthrozoology. Research focusing on this subject has begun to emerge in Russia as well. The book under review aligns well with this trend. As is indicated by the title, the book has a clear economic focus. K. Krylova aims to analyze the function of pets, their work practices, and consumption patterns associated with animals within the family context. The researcher categorizes small-sized animals that require minimal time and effort for care as “convenience pets.” The market for such pets is steadily growing, with high demand. K. Krylova essentially views them as precarious workers who provide their human companions with a unique emotional environment. However, it is worth noting that the book lacks an economic analysis. The author classifies modern Russian society as a neoliberal culture that individuals must adapt to. She emphasizes the impact of stress resulting from the nature of relationships and employment in societies and economies of this type. Specifically, she highlights a group of professionals with unpredictable work hours who delay marriage or having children and are vulnerable to various psychological issues, such as insomnia, depression, and nervous breakdown. Many of them turn to pets as substitutes for family. The author takes the concept of animals as “living anti-depressants” to its logical conclusion. She also delves into the effects of fantasy monsters found in books, movies, videogames, and microformat pets and neototems. While her analysis seems plausible, there are some limitations to consider: she primarily focuses on young professionals in creative fields and exclusively on micro-animals. It's worth noting that larger dogs, for example, can serve similar functions.